Driver education: how effective?. Issue 1 (2nd January 2020) - O'Neill, Brian
Abstract: In the early 20th century, the numbers of motor vehicles in use grew rapidly in the USA, Canada, and many European countries. By the 1930s, the number of automobile crashes and the resulting deaths and injuries was a significant problem and various safety organizations tried to address it with education and publicity programs aimed at changing driver behaviour. It is not clear when the high crash risks of young drivers were first identified, but in the early 1930s driver education courses began to be offered in US high schools (feasible because US licensing ages were 16 or younger) and soon such courses were being touted (with no evidence) as 'the most obvious way' to reduce traffic crashes. Over the years many claims were made for the effectiveness of high school driver education, however, it was not until the late 1960s that competent research studies (including randomized control trials) were undertaken. The consistent findings from these studies have been that high school driver education does not reduce crashes. Furthermore, the trained students get their licenses sooner, and because teenagers have very high crash risks, the net result of high school driver education is increased numbers of crashes.